Dendritic Cells Stimulated with Actinobacillus actinomycetemcomitans Elicit Rapid Gamma Interferon Responses by Natural Killer Cells - Kikuchi, T. (American Society for Microbiology, 2004)
Human immunoglobulin G2 (IgG2) responses are gamma interferon (IFN-γ) dependent, and monocyte-derived dendritic cells (mDCs) promote IgG2 production. DCs spontaneously emerge from monocytes in cultures prepared from localized aggressive periodontitis (LagP) patients, and these patients have high levels of IgG2 that is reactive with Actinobacillus actinomycetemcomitans. These results prompted the hypothesis that an interaction between mDCs and A. actinomycetemcomitans promotes IFN-γ production, and IFN-γ is known to promote both immunopathology and protective IgG2. A. actinomycetemcomitans induced mDCs to produce interleukin-12 (IL-12), and the addition of A. actinomycetemcomitans and DCs to cultured peripheral blood lymphocytes elicited high levels of IFN-γ within just 24 h. In contrast, IL-4 was not detectable although DC-derived IL-10 production was apparent. A. actinomycetemcomitans-stimulated macrophages prepared from the same monocytes lacked the ability to induce IL-12 or IFN-γ responses. NK cells of the innate immune system were the primary source of this early IFN-γ, although CD8 T cells also contributed some. The NK cell-derived IFN-γ was IL-12 dependent, and A. actinomycetemcomitans-DC interactions were Toll-like receptor 4 dependent. A. actinomycetemcomitans and A. actinomycetemcomitans lipopolysaccharide (LPS) were more potent than Escherichia coli and E. coli LPS in the ability to induce DC IL-12 and IFN-γ. The ability of A. actinomycetemcomitans-stimulated DCs to induce NK cells to rapidly produce IFN-γ in the absence of detectable IL-4 suggests their potential for skewing responses toward Th1. This may help explain the presence of Th1-associated cytokines in gingival crevicular fluid (GCF) from LagP patients and the high levels of IgG2 in their serum and GCF that is reactive with A. actinomycetemcomitans.